OCTAHEDRAL CRYSTALS IN PHYCOMYCES. II - Ootaki, T. (The Rockefeller University Press, 1973)
"Phycomyces blakesleeanus" sporangiophores contain octahedral crystals throughout their cytoplasm and vacuole. More octahedral crystals were found in the wild-type strain G5 (+) than in the β-carotene-deficient mutant C5 (-), and much more than in the mutant C141 (-), which is sensitive to only high light intensity. In the wild type, the number of crystals per sporangiophore increased until the sporangiophore reached stage IV, and then decreased. Stage I contained the most crystals per unit volume. Cultures grown in darkness had the maximum number of crystals. Under high light intensity, there was an overall reduction of crystals. The crystals are regular octahedrons. The crystals were isolated from the sporangiophores by a method of sucrose density-gradient centrifugation. They contain nearly 95% protein, are stable in organic solvents, but can be solubilized in buffer solution above pH 9.5 and below 2.5. The crystals weakly fluoresce with an emission peak at 540 nm, which is affected by irradiation with white light. Absorption spectra of freshly prepared crystals show absorption maxima around 265–285 nm, 350–380 nm, and 450–470 nm. These absorption peaks for the crystals are close to those of the phototropic and light-growth action spectra. These data suggest that the crystals may contain a flavoprotein which may be the photoreceptor pigment of "Phycomyces".